2002
DOI: 10.1080/02701367.2002.10609017
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Movement Skills: Predictors of Physical Activity in Anglo American and Mexican American Adolescents?

Abstract: We assessed the relationship between young children's movement skills and their physical activity in early adolescence. Balance, agility, eye-hand coordination, and skinfold thicknesses in 207 Mexican American and Anglo American children (104 boys, 103 girls) were measured at ages 4, 5, and 6 years. Habitual physical activity was assessed at the age of 12 years by two interviewer-administered 7-day recalls. Ethnic differences in movement skills were not found. Young girls were better at jumping and balancing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 13 publications
10
106
0
4
Order By: Relevance
“…However, the latter relationship did not remain significant after controlling for confounders. In contrast to our data, a few longitudinal studies in school children and adolescents found that motor skills were important determinants of reported PA. 5,43 Our results are more in line with the findings reported by McKenzie et al, 44 who also included younger children and found that baseline motor skills (including agility, balance and coordination) were not related to their reported PA 6 years later. The inconsistencies between previous longitudinal studies could be explained by differences in age, the lack of controlling for baseline values, the lack of objective measures of PA and differences in the selected motors skills and tests.…”
Section: Determinants Of Pa Changessupporting
confidence: 83%
See 1 more Smart Citation
“…However, the latter relationship did not remain significant after controlling for confounders. In contrast to our data, a few longitudinal studies in school children and adolescents found that motor skills were important determinants of reported PA. 5,43 Our results are more in line with the findings reported by McKenzie et al, 44 who also included younger children and found that baseline motor skills (including agility, balance and coordination) were not related to their reported PA 6 years later. The inconsistencies between previous longitudinal studies could be explained by differences in age, the lack of controlling for baseline values, the lack of objective measures of PA and differences in the selected motors skills and tests.…”
Section: Determinants Of Pa Changessupporting
confidence: 83%
“…The inconsistencies between previous longitudinal studies could be explained by differences in age, the lack of controlling for baseline values, the lack of objective measures of PA and differences in the selected motors skills and tests. For example, some studies tested locomotion, agility and balance, 43,44 whereas another study, additionally tested object control skills or fine motor development. 5 In this study, not all relevant motor skills for this age group were tested.…”
Section: Determinants Of Pa Changesmentioning
confidence: 99%
“…More Whites reported being physically active than Latinos in study of 1119 randomly selected sixth-and seventhgrade California students (Carnvajal et al, 2002). However, McKenzie et al (2002) found no differences in movement skills between Mexican and Anglo-American children. Importantly, the intervention in the current study improved both physical activity and dietary fat for subjects in each racial group.…”
Section: Limitationsmentioning
confidence: 72%
“…agreement for all 187 items (percentage agreement 95%, k = 0.84). Seventeen of the 22 studies used measures of FMS proficiency that had published validity, 14,33,[35][36][37][38][39][40][41][42][43][44][46][47][48][49]52 and this was the most commonly reported item across the studies. Nine studies met the criteria for adequate retention.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…11 There is also longitudinal evidence that motor skills track through childhood 12,13 and into adolescence. 14,15 FMS proficiency has been associated with subsequent physical activity 16 and also with change in physical activity over time, highlighting that children with high FMS proficiency show little decline in physical activity. 17 In addition, positive associations have been established between FMS proficiency and objectively measured physical activity in overweight children.…”
mentioning
confidence: 99%